HUBUNGAN INDEKS MASSA TUBUH DENGAN DAYA TAHAN ANAEROBIK - Fajri Yuga; Andi Atssam Mappanyukki; Etno Setyagraha; Hasmyati Hasmyati (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
In sports, there are many aspects that must be considered so that athletes can achieve maximum performance, one of which is anaerobic endurance. Especially in one of the teams in Kab. Enrekang is a 3BFC Futsal team which according to the coach, the team's performance has tended to decline in the last 2 years. The method used to collect data is by test and measurement techniques. The instrument used is a measurement using Body Mass Index (BMI) and the RAST (Running-Based Anaerobic) test from the sample. The population in this study is Futsall 3BP FC players. Descriptive analysis technique using Normality Test and Correlation Test. From the results of the research, data analysis obtained Pearson Correlation value of 0.748 and P value of 0.025 (P <0.05) Ho is rejected, Ha is accepted. This shows that there is a significant relationship between body mass index and anaerobic endurance in 3BP FC futsal players.